Pronunciation of English Words Displayed in Public Spaces by Indonesian Non-Native English Speakers - Damianus Talok; Aplonia Nelci Ke Lomi; Maria Regina Jaga (International Journal of English and Applied Linguistics (IJEAL), 2024)
The study used a descriptive qualitative design to explore the pronunciation of English words in public spaces in Kupang City, Indonesia. Data were collected from ten local respondents, predominantly Timorese, through field observations and interactions on public roads. The research documented and analyzed 152 English words found in hotels, billboards, supermarkets, stores, public transportation, and food establishments. The analysis focused on the locals' pronunciation of these words, revealing variations and humorous elements that highlight unique aspects of language use. The findings underscored the widespread presence of English and other foreign languages in the city's public spaces. They demonstrated the pronunciation challenges faced by non-native speakers, particularly Indonesian speakers, with limited exposure to English. The study provided insights into the influence of English on rural life in Indonesia and how locals navigate and express identity through language. It contributed to understanding the role of English as a global language in non-native English-speaking regions, emphasizing the diverse pronunciation patterns encountered in such contexts.